1993
DOI: 10.2527/1993.71123339x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle cellularity and postnatal growth in the pig1

Abstract: Fast-growing strains of pigs and of other animals tend to have more muscle fibers than do slow-growing strains. The relationship between fiber number and growth rate was extended by examining pigs within the same strain. Seven litters of pigs (n = 66) were weighted at monthly intervals from birth to approximately 80 kg. The semitendinosus muscle was removed and an estimation of total fiber number, total primary fiber number, and mean secondary:primary fiber number (S:P) ratio was made for each animal. Pig grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
2
13

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 19 publications
14
91
2
13
Order By: Relevance
“…Previous studies have demonstrated that larger piglets usually grow faster than their lighter littermates (Powell and Aberle, 1980;Dwyer et al, 1993), but the findings of the present study do not support this. Despite litter size being similar between L and N groups, there was a tendency for L mothers to rear fewer offspring compared to their N counterparts, but this was in part due to the occurrence of cross-fostering (decision made by the Pig Unit Management).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have demonstrated that larger piglets usually grow faster than their lighter littermates (Powell and Aberle, 1980;Dwyer et al, 1993), but the findings of the present study do not support this. Despite litter size being similar between L and N groups, there was a tendency for L mothers to rear fewer offspring compared to their N counterparts, but this was in part due to the occurrence of cross-fostering (decision made by the Pig Unit Management).…”
Section: Discussioncontrasting
confidence: 99%
“…Dwyer et al (1992) suggested that a reduction in placental size might be the mechanism mediating negative effects of maternal undernutrition on birth weight and the number of secondary muscle fibres in the offspring (Handel & Stickland 1987, Dwyer et al 1994. Consistent with the earlier data of Hegarty and Allen (1978) indicating that runts have reduced muscle growth potential and needed 23 days longer to reach a weight of approximately 105 kg, Dwyer et al (1993) established a positive correlation between the total number of muscle fibres and postnatal growth potential. Furthermore, the effect of maternal nutrition was identified as occurring between days 25 and 50 of gestation, the period immediately preceding secondary muscle fibre hyperplasia (Dwyer et al 1994).…”
Section: Introductionsupporting
confidence: 78%
“…Although the scope of the present experiment did not allow analysis of postnatal growth effects, earlier studies (Handel & Stickland 1987, Dwyer et al 1993, 1994 have clearly demonstrated reduced postnatal growth potential due to quantitative effects on fetal muscle development through maternal undernutrition. The results of the present study extend the findings of previous work in the pig in which both naturally occurring IUGR within a litter (Aberle 1984) and nutritional manipulation during gestation (Dwyer et al 1994) preferentially affected secondary muscle fibre development.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are consistent with those reported earlier (Lefaucheur et al, 2002 and2004). These slow fibres are also defined as primary fibres, and the number and size of these fibres determine muscle mass and individual size in mature animals (Wigmore and Stickland, 1983;Stickland and Handel, 1986;Dwyer et al, 1993).…”
Section: Discussionsupporting
confidence: 91%